Peningkatan Keterampilan Menulis Teks Biografi Dengan Menggunakan Media Infografis Pada Peserta Didik Kelas X di SMA IT Izzuddin Palembang - Suryani, Anggi; Lestari, Hikmah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The aim of PTK research is to improve skills in writing biographical texts using infographic media. The background for conducting this research was the low ability to write biographical texts for class X students at SMA IT Izzuddin Palembang. The research method used is quantitative. This research uses stages in PTK research, namely planning, action, observation and reflection. The data analysis used in this research used comparative descriptive techniques and data collection in the form of tests and non-tests. Activities are carried out over two cycles and each cycle has one meeting. Based on this research, it was concluded that there was an increase in skills in writing biographical texts using infographic media in two stages and the average value increased for each cycle, namely cycle I (70.9) and cycle II (85.8). In cycle II activities, student behavior was classified as very good because there was a change in behavior of up to 95%. Therefore, it can be concluded that there is an increase in both biographical text writing skills and changes in students' behavior towards a better direction during learning activities.